Mean recurrence interval as a criterion for the determination of design wind load on structures in the Metro Manila area - Villasenor, Vinci Nicholas R.
The thesis presents some probabilistic methods of determining the basic design wind load as an alternative to the current deterministic wind speed of 175 kph for the Metro_manila area as specified by the National Structural Code for Buildings (NSCB). Other engineering codes have recognized the need to specify wind loading based on the probabilistic concepts consisted with the code's objective of providing consistent and adequate levels of safety. The mean recurrence interval as the design criterion for the determination of wind loading is proposed in keeping with the continuously improving standards of other engineering codes.